Hyperglycemia Alters the CD27:CD70 Axis of Human Immune Cells. (9th November 2022) - Lerret, N; Owaja, C; Schulz, M; Roback-Navarro, E
Abstract: Introduction/Objective: The exact mechanism that inflammation plays in the pathogenesis from obesity to Type 2 diabetes is unclear, however, activated immune cells and pro-inflammatory cytokines have been found in the adipose tissue of Type 2 diabetics, implicating their role in the disease process. While the CD27-CD70 axis is being explored in other models of chronic inflammation, such as rheumatoid arthritis and colitis, the role played in Type 2 diabetes remains unknown. Objective: Evaluate whether hyperglycemia alters immune cells phenotype and effector function, specifically of the CD27:CD70 axis on human immune cells. Methods/Case Report: Human peripheral blood from donors was divided into three groups. n=40 total those that have a healthy blood glucose value and are without any co-morbidities (normoglycemic), patients identified as having pre-diabetes per their hemoglobin A1c (HgbA1c) value (5.6-6.5%), and patients with diabetes, having an elevated blood glucose and HgbA1c value (> 6.5%). The blood was then stained with monoclonal antibodies towards cell surface markers associated with inflammation, including CD27/CD70 and analyzed via flow cytometry. Previous data using cell cultures of human PBMC-derived T cells and autologous dendritic cells exposed to varing concentrations of glucose to simulate hyperglycemia and pre-diabetes was compared to this data. Results (if a Case Study enter NA): 1) T cells directly analyzed from pre-diabetic and hyperglycemia individuals down-regulate their CD27 expression. CD70 is up-regulated on immune cells directly analyzed from pre-diabetic individual when compared to immune cells from normoglycemic individuals. In accordance with the above resutls, CD4 T cells have an activated effector phenotype after co-culture with glucose stimulated dendritic cells. This includes down-regulation of CD27 on T cells and up-regulation of CD70 on dendritic cells. Conclusion: Our data shows that certain markers of inflammation are up-regulated on the surface of immune cells from pre-diabetic and/or diabetic patients. Specifically, we demonstrate novel evidence that the CD27-CD70 axis is activated in diabetes or hyperglycemic conditions. These molecules may offer a potential target for therapeutics. Alternatively, our findings would allow a further way to characterize where a patient with an elevated blood glucose value is on the spectrum between pre-diabetes and full-blown diabetes.